Education On Flood Disaster Management And Its Impact On Health In Rt 25 Sawah Lebar District Ratu Agung District Bengkulu City - Charolin; Nurjana, Nurjana; Ariyatama, Wiga; Agustya, Gita; khasanah, Uswatun; Wulandari, Wulandari (Universitas Dehasen Bengkulu, 2024)
. Flooding is a seasonal threat that occurs when a body of water overflows from an existing channel and inundates the surrounding area. Disasters are common occurrences in the world, and their causes may be natural, man-made, technological or conflicts between human groups. Lack of education on flash flood prevention is one of the factors that cause risk. Flooding is also a problem because it can affect sectors of people's lives, especially health. The health problems that arise due to flooding include diarrhea, dengue fever, leptospirasis, ARI, skin diseases, digestive tract diseases and so on. The purpose of this counseling activity is to provide education to residents in the RT 25 neighborhood area of Sawah Lebar Village about knowledge related to flood disasters. The method used in the research through Flood Disaster Counseling Activities was carried out with cerama Results and Discussion in this KKN activity with the title “Disaster Counseling in Rt. 25 Sawah Lebar Village, Bengkulu City”.The results obtained after this counseling activity are an increase in community knowledge in the RT 25 neighborhood area of Sawah Lebar Village, Bengkulu City on the prevention of flash floods. Suggestion: As a result of this flood disaster counseling activity, it is hoped that the community will gain knowledge about disasters